2006
DOI: 10.1016/j.adolescence.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between maternal and paternal psychological symptoms and ratings of adolescent functioning

Abstract: Families with an adolescent between the ages of 11 and 18 years participated in a study examining the relationship between parental depressive and anxiety symptomatology and parental ratings of adolescents’ functioning. This study indicated that mothers, fathers, and adolescents exhibited significant cross‐informant correspondence (i.e. correlations) and very few significant differences in ratings of adolescents’ functioning. After controlling for demographic variables and the ratings of other informants, moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
(57 reference statements)
4
13
1
3
Order By: Relevance
“…In contrast, these discrepancies have not been found in the ratings of mothers who are not depressed or anxious (Najman et al 2000). Similar findings are beginning to be documented for fathers (e.g., Renk et al 2007). Various explanations for why parents exhibiting psychological distress have a tendency to report greater levels of behavioral problems in their children have been proposed.…”
contrasting
confidence: 43%
See 1 more Smart Citation
“…In contrast, these discrepancies have not been found in the ratings of mothers who are not depressed or anxious (Najman et al 2000). Similar findings are beginning to be documented for fathers (e.g., Renk et al 2007). Various explanations for why parents exhibiting psychological distress have a tendency to report greater levels of behavioral problems in their children have been proposed.…”
contrasting
confidence: 43%
“…For example, research has documented a relationship between parents' psychological symptoms (i.e., depression and anxiety) and their ratings of children's emotional and behavioral problems (Fergusson et al 1993;Moretti et al 1985;Najman et al 2000;Renk et al 2007). In general, these studies have suggested that mothers who are depressed or anxious tend to rate their children as experiencing higher levels of emotional and behavioral problems.…”
mentioning
confidence: 99%
“…Selon certains, une structure factorielle à trois facteurs, soit l'un ayant trait à la régulation comportementale, un autre à la métacognition et le dernier à la régulation émotionnelle, permettrait de rendre compte davantage de variance expliquée (Egeland & Fallmyr, 2010;Peter, Algina, Smith, & Daunic, 2012 . Il pourrait y avoir un lien entre la détresse psychologique du parent et le fait qu'il tend à rapporter davantage de problèmes par rapport au fonctionnement de l'enfant (Grietens et al, 2004;Phares, 1997;Renk et al, 2007 Une autre limite de cette étude a trait à la représentativité de l'échantillon par rapport à la répartition de la DI dans la société. D'abord, il n'a pas été possible de considérer le type de syndrome dans les analyses en raison du peu de fiabilité de l'information disponible.…”
Section: Instruments Fonctions Intellectuelles Les Fonctions Intelleunclassified
“…(Grietens et al, 2004;Phares, 1997 ;Renk et al, 2007). De plus, avoir un enfant avec une DI augmente les risques pour les parents de vivre de la détresse .…”
Section: Wechsler Adult Intelligence Scale -Third Edition (Wais-iii)unclassified
“…La vulnérabilité psychologique des parents et, particulièrement des mères d'enfants ayant une DI, pourrait expliquer le fait que celles-ci tendent à rapporter davantage de problèmes de comportement que les autres observateurs . Le stress familial, souvent retrouvé dans les familles avec un enfant ayant une DI, pourrait être lié à leur perception des troubles de comportement (Renk et al, 2007). Il est possible que les parents éprouvant de la détresse, soient plus sensibles aux problèmes de comportement d'un enfant et qu'ils tendent à en relever davantage.…”
Section: Wechsler Adult Intelligence Scale -Third Edition (Wais-iii)unclassified